A detection and diagnosis method for tubing leakage below liquid level in gas wellbore. (October 2022) - Wu, Shengnan; Fan, Jianchun; Yang, Yunpeng; Zhang, Laibin; Ma, Fanfan
Highlights: The optimized tubing leakage simulation platform has the advantages of leakage visualization, flow stability and controllability. A leakage recognition model is established for annulus below liquid level based on SVM. Acoustic detection method is used to identify the leakage below the annulus liquid level. Abstract: The accurate detection and diagnosis of the position of tubing leakage above or below the liquid level plays an important role in the emergency response to the leakage. This paper presents a new detection and diagnosis method based on acoustic monitoring tubing leakage below the liquid level. The optimized simulation experiment system for tubing leakage was proposed with visualization and controlled flow rate design, and it can capture the annular acoustic characteristics of leakage above and below the liquid level. The leakage identification model is established by optimizing multi-dimensional acoustic characteristic parameters. The results show that when the leakage occurs above and below the liquid level, the distribution of leakage noise in time domain and frequency domain is quite different. Such model can quickly and accurately diagnose whether the leakage of wellbore tubing occurs above or below the liquid level with an accuracy rate of 99.32 %.